Los bicentenarios de independencia de América Latina en 2021 - Pedro Pérez Herrero (Caravelle)
In 2021 the activities and speeches which celebrated the bicentenaries of Latin American independences were complemented in certain countries by a strong radicalisation. This paper explains why this process took place in 2021 and proposes what should be done to prevent historiographical accounts from promoting exclusion nationalism favouring instead the creation of plural and inclusive societies.